The IMPLEMENTASI APLIKASI PUSAT PERTUKARAN DATA PADA SISTEM PERADILAN PIDANA TERPADU BERBASIS TEKNOLOGI INFORMASI (SPPT-TI) - Muijyanto, Tri Ragil; Maukar, Maukar (Journal of Information System, Applied, Management, Accounting and Research; Vol 5 No 2 (2021): JISAMAR : Volume 5, Nomor 2, May 2021, 2021)
The 2015-2019 National Medium Term Development Plan (RPJMN) mandates that one of the policy directions for law and human rights development in the context of realizing quality law enforcement is to promote an integrated criminal justice system that is implemented through the development of an Information Technology-based Integrated Criminal Justice System (SPPT-TI). In the process of handling criminal cases, sending files between Law Enforcement Officials (APH) takes a long time and is less efficient, so it requires a variety of response times. Broadly speaking, SPPT-TI aims to optimize the use of information technology in the process of handling criminal cases in terms of exchanging data and information between institutions involved in the criminal justice system. In the development process, the Puskarda application uses the DevOps development method which is quite appropriate to the conditions in the field which require periodic improvement. The Puskarda application is used to exchange data and documents electronically at SPPT-TI and ensure that the data exchange process between APHs involved is in accordance with the SPPT-TI data exchange guidelines. It is hoped that this research can help explain the stages in implementing the Puskarda application and can find out the constraints in exchanging data in order to improve application performance to meet the needs of application users